Determinants of stock market development: evidence from advanced and emerging markets in a long span - Evrim-Mandaci, Pınar; Aktan, Bora; Kurt-Gumuş, Guluzar; Tvaronavičienė, Manuela (Business: Theory and Practice, 2013)
The paper analyses determinants of stock market development in thirty advanced and emerging countries within the period between 1960 and pre-financial global meltdown (2007). Our explanatory variables are foreign direct investment (FDI), remittances and bank credits to private sector. The application of SUR estimation disclosed that all variables had significant positive effects on market development measured by market capitalization. The obtained results unfolded the necessity for the countries to develop policies and regulations on facilitating FDI, remittances and bank credits.